2020
DOI: 10.1039/c9dt04082j
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and cationic enantiopure group 13 iminophosphonamide complexes

Abstract: Utilising the enantiopure iminophosphonamide ligand the enantiopure group 13 metal complexes have been synthesised. The cationic complexes have been accessed using halide abstraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…As with carbon-supported aluminum hydride systems, a common reactivity pathway is the hydroalumination of organic π-bonds. Given the plethora of new N -donor aluminum hydride systems reported in the past two decades, , this section will aim to focus on the new bonding motifs and reactivity pathways uncovered in this area.…”
Section: Molecular Hydrides Of Group 13 Metals (Aluminum Gallium Indi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As with carbon-supported aluminum hydride systems, a common reactivity pathway is the hydroalumination of organic π-bonds. Given the plethora of new N -donor aluminum hydride systems reported in the past two decades, , this section will aim to focus on the new bonding motifs and reactivity pathways uncovered in this area.…”
Section: Molecular Hydrides Of Group 13 Metals (Aluminum Gallium Indi...mentioning
confidence: 99%
“…841 Reactivity-wise, few reports of the chemistry of isolated indium hydride species have been published, although their in situ generation and applications in organic synthesis (e.g., as a radical initiator) have been discussed (see also Section 5.4.3). 875−877 Halide/hydride exchange has been reported for the quinuclidine adduct (quin) 2 InH 3 (693) in the presence of LiBr, initially generating (quin) 2 InH 2 Br (694). Compound 694 subsequently undergoes reductive dehydrogenation and disproportionation to generate the mixed valence penta-indium cluster [In 5 Br 8 (quin) 4 ] − , as the [H(quin) 2 ] + salt (695).…”
Section: And Scheme 1 0 0 ) T H E I N D I U M S Y S T E M [ L I ( T ...mentioning
confidence: 99%
“…Very recently, we have synthesized a chiral version of an iminophosphonamide ligand ( L ‐H) and found that it allows further derivatization into alkali and group 13 metal complexes [5b, 6] . The complexes [M 2 ( L ) 2 ] (M=alkali metals, Figure 1) showed exciting photoluminescence (PL) properties, including bright long‐lived phosphorescence at low temperature and thermally activated delayed fluorescence (TADF) with a high quantum yield at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the length of the Ga–Cl bond lies in its typical range. The gallium atom in n Bu 8 PcGaCl has a coordination number of 5, which is rare for gallium complexes. …”
Section: Development Of the Catalytic Strategymentioning
confidence: 99%